Performance of Holstein heifers reared on 100 or 115% of NRC requirements from 3 to 12 months of age and then switched to the opposite treatment - E. J. Bortone; M. G. Daccarett; J. L. Morrill; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1991)
Holstein heifers from the Kansas State University Dairy Teaching and Research Unit were used from 3 mo of age until 21 d before estimated date of calving. They were fed either 100 (control, C) or 115% (enhanced, E) of the 1989 National Research Council (NRC) requirements for major nutrients from 3 to 12 mo of age, then, until 21 d before freshening, the treatments were switched from 100 to 115% NRC (CE) or from 115 to 100% NRC (EC). At puberty, heifers had similar body weights (613, E vs 617, C) but heifers fed E were 1 month younger (11 vs 12 mo). Heifers fed the E diet were heavier and had larger heart girth at 12 mo of age than the group fed C. After switching, the group fed CE increased more in body weight, body length, wither height, and body condition than the group fed EC.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Heifer; NRC; Switch; Puberty; Diet